The Impact of Interprofessional Education on Health Profession Students' Professional Identity - Gioia J. Ciani; Gary Grimaldi; Maribel Macalintal; David Orner (MDPI AG, 2023)
Establishing interprofessional identity is critical in preparing health care teams to work in collaborative environments and enhance efficacy of patient care. Accreditation standards for health profession programs have been implemented to include interprofessional education (IPE), yet there remains obfuscation regarding occupational therapy's (OT) professional identity. The purpose of this prospective pre-post test study was to assess an experiential IPE event for health profession students (n = 170 from ten health profession programs) to: (1) determine the effectiveness of role playing and team-based case discussions on students' knowledge and perceptions toward each other's professions, and (2) specifically assess the impact of the IPE event on students' perceptions toward OT roles and responsibilities. Health profession students were asked to complete a survey prior to and at the conclusion of the IPE event, which included the validated Interdisciplinary Education Perception Scale (IEPS) and non-standardized closed and open-ended questions. Quantitative analysis of responses showed a significant improvement in interdisciplinary perceptions after the experience as evidenced by higher IEPS scores. Post-test open-ended responses confirmed this finding. Health profession programs were stratified, revealing positive significant differences regarding OT. These findings suggest role-playing and team-based case discussions for IPE can have a positive impact on students' interprofessional perceptions and understanding of OT.